The African Union and its regional economic communities confronted with coups d’état: between condemning and condoning - Iragi Ntwali, Valéry (Frontiers in Political Science, 2025)
The African Union and its regional integration bodies have experience a long tradition of coups d’état perpetrated in their member states. Aimed at democratizing the continent, these organizations have adopted democratic norms and values that prohibit coups d’état, to the extent that today it is possible to outline a mosaic of democratic norms and institutional mechanisms designed to achieve this purpose in Africa, but with mixed results. This paper sets out to analyze the various causes and obstacles that create a fertile ground for coups d’état to persist in some African states. It also identifies the institutional, decision-making and operational challenges that prevent the African Union and its regional organizations from successfully preventing or stemming out coups. Based on a historical, institutional and strategic analysis, the study reveals that the failure of democratic transition, and economic and security policies at national level has an impact at regional level. It also reveals that due to the lack of institutional autonomy and the predominance of sovereign choices made by some member states, the African Union and its regional organizations are powerless to address the situation of coups d’état. Although African Union and its regional integration organizations are trapped in a delicate situation regarding their institutional and functional autonomy, they would at least save their legitimacy vis-à-vis the citizens of their member states if they firmly condemned all forms of coups d’état including constitutional or electoral ones. Their effective actions against coups d’état remains dependent on the willingness of Member States to submit to Community norms and decisions without brandishing the attributes of sovereignty that would lead to exits from the regional organization. The Conferences of Heads of State, which are the decision-making and guiding bodies within the African Union and its regional integration organizations, will only be effective against coups d’état, and by extension the organizations themselves, if some of those chair them do not or have not remained in power through a coup d’état.